(3eHOC GdMQjI GdfbGHjI Hjf GdhMOI hGdJYOO (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdeUQj hGdbGfhf GdeZQHj (B/ s - (3fhRgI GdMVQGejs; (3CMeO MSf GdHQYj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3ef NdGd HMK eHOC GdhMOI hGdJYOO GdfbGHj GdebQQ HebJVj GdGJaGbjGJ hGdehGKjb GdOhdjI hGdYQHjI(B: (3Ydj eSJhj GdJTQjYjf GdeUQj hGdeZQHj(B: (3NdUfG Gdj Gfg HGdQZe ef GNJdGa fWGb GNP cd efgeG HeHOC GdhMOI hGdJYOO(B: (3ef NdGd JHfj GdChd hMOI GdJfXje hGYJeGO GdKGfj deHOCGdJYOO GdfbGHj(B: (3aEf GhVGY GdMQcI GdfbGHjI ajgeG eJTGHgI Gdj MO cHjQ(B: (3ef MjK JQGLY OhQ GdfbGHI aj JCWjQ GdYeGds
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2008.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B196 - 204.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdGLJeGYjIs; (3GdMQjI GdfbGHjIs; (3fTCI GdMQjI GdfbGHjIs; (3GdhMOI hGdJYOOs; (3efXeI GdYed GdOhdjIs; (3UjGfI GdMbhb GdfbGHjIs; (3efXeI GdYed GdYQHjIs; (3eHOC GdGNJjGQ GdfbGHjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs